The Synthesis of Bio-Polyol from Epoxidized Soybean Oil - Thuy, Nguyen Thi; Duc, Vu Minh; Liem, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4DO - 10.25073/2588-1140/vnunst.4511, 2017)
Abstract: Hydroxyl and oxirane functionality were calculated from molecular weight and hydroxyl or oxirane-oxygen content of polyol. The effect of reaction parameters like the amount of reagents, catalyst, temperature and time on a polyol synthesis was studied through the hydroxyl and oxirane functionality of product. Moreover, the impact of the parameters on the selectivity of catalyst was determined by comparing a polyol yield to an epoxide ring opening yield. When the hydroxylation reaction was carried out with ESO:H 2 O molar ratio of 1:15; in 8 wt.% of H 2 SO 4 ; at temperature of 70 o C and in 5 hours, the polyol yield of reaction was 70.32%Â  andÂ  the hydroxyl functionality of polyol reached to 5.63